Diego Venturino (éd.), OEuvres complètes de Voltaire - Sfoini, Alexandra (The Historical Review/La Revue Historique, 2021)
Review of: Olga Katsiardi-Hering (ed.), Βενετικοί χάρτες της Πελοποννήσου, τέλη 17ου–αρχές 18ου αιώνα: Από τη συλλογή του Πολεμικού Αρχείου της Αυστρίας [Venetian maps of the Peloponnese, late 17th–early 18th centuries: From the Austrian War Archive collection]